A new multistep Si{1 0 0} machining process for aspheric cavities: the role of high-index surfaces - Wilfrido Calleja-Arriaga (Academia Materials Science)
Bulk silicon (Si) micromachining in the {1 0 0} family of planes, despite its apparent simplicity, remains an effective process for developing increasingly diverse microstructures and applications. Based on fourfold crystal symmetry and aqueous potassium hydroxide (KOH) solutions, this Si micromachining technique supports microlens fabrication, provides predictable sagitta, and enables matrix array systems for engineering and micro-optics applications. The central mechanism involves two-step etching over a single or matrix pattern to achieve reproducible aspheric cavities; this process is typically performed on planar substrates. Typical cavities are characterized by a continuous high-index concave surface with an unknown overall morphology. Regarding microlens fabrication, we note the lack of thorough studies on this type of concave structure, particularly when another pattern is machined over the aspheric surface. By adding lithography and etching steps to this well-known process, the aspheric morphology can be improved. This work presents a novel multistep micromachining technique on (0 0 1) Si substrates for the fabrication of modified aspheric cavities. The approach makes use of sequential patterns imprinted over the partially developed microcavities, enabling a localized etching mechanism influenced by the aspheric morphology. The sequential morphologies are analyzed and described, with the peculiar etching mechanisms crystallographically analyzed. Finally, some applications related to surface physics and micro-optics are discussed in the context of these novel microstructures.